La società diseguale del fascismo. Politiche scolastiche, mobilità sociale e frattura generazionale - Gagliardi, Alessio (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
While Fascism celebrated youth as the embodiment of the “new man” and as a metaphor for vitality, its policies—particularly educational reforms—aimed to consolidate social hierarchies and restrict upward mobility. Focusing on middle-class youth, especially professionals and public employees, the essay analyses the persistent phenomenon of intellectual unemployment, rooted in structural imbalances between educational output and labour market absorption. The regime failed to resolve these tensions, which were further exacerbated by economic constraints and corporative lobbying. The study highlights how ideological aspirations clashed with social realities, shaping patterns of inequality and exclusion throughout the Fascist period.